Luteolin mitigates proliferative vitreoretinopathy through inhibition of ERK1/2 signaling and epithelial–mesenchymal transition - Wu, Lingdan; Chen, Meiling; Chai, Jinghua; Tang, Yujie; Xu, Qihua (Frontiers in Pharmacology, 2026)
AimTo investigate the inhibitory effect of luteolin on proliferative vitreoretinopathy (PVR) and explore its potential mechanism.MethodsHuman retinal pigment epithelial ARPE-19 cells were treated with luteolin (0–50 μM) to assess its effects on cell viability, migration, and TGF-β2–induced epithelial–mesenchymal transition (EMT). Cell viability (CCK-8), Scratch and Transwell assays, flow cytometric cell-cycle analysis, immunofluorescence, and Western blotting were performed to evaluate α-SMA, vimentin, and p-ERK1/2 expression. In vivo, a PVR mouse model was established by intravitreal injection of ARPE-19 cells combined with platelet-rich plasma (PRP). Mice received a single intravitreal injection of luteolin (1 μL, 20 μM) or PBS on day 3, and retinal tissues were collected 28 days later for histological and protein analyses.ResultsOur results revealed that luteolin, at concentrations of 12.5 μM and 25μM, significantly inhibited the horizontal and vertical migration ability of ARPE-19 cells. Luteolin, at concentrations of 12.5 μM and 25μM, also effectively inhibited the expression of EMT-related mesenchymal proteins induced by TGF-β2 in ARPE-19 cells. Luteolin inhibited intraocular mesenchymal proteins increase in experimental PVR in mice, followed by downregulation of p-ERK1/2 protein expression.ConclusionLuteolin suppresses RPE cell migration and EMT both in vitro and in vivo, thereby alleviating PVR development. Its protective effect is associated with downregulation of ERK1/2 signaling. The inhibitory effects of luteolin suggest its potential as a therapeutic agent for PVR.